High-performance layer structure PVC door curtain and preparation method thereof

By combining fluorosilicone bifunctional group synergistic grafting modification with organic small molecule reinforcing agents, a molecular layer structure with polar gradient distribution is formed, which solves the problems of embrittlement and poor interlayer bonding of traditional PVC door curtains at low temperatures, and achieves improved transparency and anti-aging performance.

CN121406069APending Publication Date: 2026-01-27HENAN XIEREN SAFETY SCREENS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511800611.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-02
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Traditional PVC curtains are prone to embrittlement at low temperatures, have poor flexibility, are susceptible to plasticizer migration, have insufficient anti-aging properties, and have poor interlayer bonding, making it difficult to balance flexibility, transparency, and weather resistance.

Method used

By using fluorosilicone bifunctional groups to synergistically graft and modify polyvinyl chloride resin, combined with organic small molecule reinforcing agents, a molecular layer structure with a polar gradient distribution is formed through π-π stacking and hydrogen bonding, thereby improving the flexibility of molecular chains and the interlayer bonding force.

Benefits of technology

It significantly improves the low-temperature toughness, transparency, and anti-aging properties of the door curtain, extends its service life, and enhances its application stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121406069A_ABST
    Figure CN121406069A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of high polymer materials, and relates to a high-performance layer structure PVC door curtain and a preparation method thereof. According to the door curtain, modified polyvinyl chloride resin is used as a matrix, and a polar gradient layered structure is formed by molecular chains through fluorine-silicon bifunctional group synergistic grafting modification; meanwhile, small organic molecule 2-vinyl-4-hydroxyacetophenone is introduced as a reinforcing agent, and a stable network is formed between layers through pi-pi accumulation and hydrogen-bond interaction. The door curtain is prepared from modified polyvinyl chloride resin, 2-vinyl-4-hydroxyacetophenone, epoxidized soybean oil, dioctyl phthalate and an auxiliary agent through blending granulation and three-layer co-extrusion molding. The structure effectively improves the interfacial compatibility and molecular arrangement uniformity, so that the material has high transparency, excellent flexibility and strong interface bonding force at the same time. The light transmittance of the prepared door curtain reaches 93% or above, the door curtain still keeps flexibility at 40 DEG C, the peel strength is high, the ultraviolet aging resistance is remarkably superior to that of a traditional PVC product, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite materials technology, specifically relating to a high-performance layered PVC door curtain and its preparation method. Background Technology

[0002] Polyvinyl chloride (PVC) curtains are flexible, transparent materials made primarily of PVC resin through plasticizing, compounding, and extrusion molding. They are widely used in cold storage facilities, cleanrooms, food processing areas, and as insect and dustproof partitions. Although traditional curtains offer good transparency, barrier properties, and cost-effectiveness, their performance is still limited by the material's structure, resulting in significant shortcomings. Ordinary PVC molecules have strong polarity and a high glass transition temperature. At low temperatures, chain segment activity is restricted, causing the curtains to become brittle and prone to breakage below -20 degrees Celsius, significantly reducing their flexibility. Traditional plasticizing systems typically use phthalates or epoxidized vegetable oils as external plasticizers to improve flexibility. However, due to poor compatibility with the PVC backbone, these plasticizers migrate or precipitate after long-term use, causing the curtain surface to become hazy, sticky, and less transparent. Light and heat-oxidation can also cause the PVC to undergo dehydrochlorination, forming conjugated double bonds, leading to yellowing, brittleness, and a shortened lifespan.

[0003] Some existing products improve overall performance through lamination or co-extrusion composite structures, but the layers are mostly physically bonded with significant polarity differences. Under thermal cycling or bending impact, they are prone to delamination and peeling, resulting in insufficient interfacial bonding and affecting long-term stability. Existing modification schemes often use inorganic fillers, polyester blends, or surface coatings to enhance performance, but these generally suffer from complex processes, reduced transparency, and high costs, making it difficult to achieve a balance between flexibility, transparency, and weather resistance.

[0004] Currently, there are no publicly reported applications of combining fluorosilicone bifunctional grafted polyvinyl chloride (PVC) with small-molecule organic reinforcing agents possessing π-π stacking and hydrogen bonding effects for use in door curtain materials. By introducing a polar gradient structure and interfacial energy matching at the molecular level, the molecular chain flexibility and interlayer bonding strength of the PVC system can be significantly improved. This allows for the enhancement of its cold resistance and anti-aging properties while maintaining high transparency, providing a new technical approach for the development of high-performance layered door curtain materials. Summary of the Invention

[0005] To overcome the problems of existing PVC door curtains, such as brittleness at low temperatures, poor flexibility, plasticizer migration, insufficient anti-aging properties, and poor interlayer bonding, the present invention aims to provide a high-performance layered PVC door curtain and its preparation method. The present invention uses PVC resin as the main body and modifies it by synergistic grafting of γ-glycidyl etheroxypropyltrimethoxysilane with 3,3,4,4,5,5-hexafluoroglutaric acid to obtain a molecularly layered PVC resin with a polar gradient distribution. The modified PVC resin is then compounded with 2-vinyl-4-hydroxyacetophenone, epoxidized soybean oil, dioctyl phthalate, and various additives, and the resulting product is melt-blended and co-extruded in three layers to obtain the layered PVC door curtain. This invention achieves molecular chain softening and interface polarity optimization through fluorosilicone synergistic grafting, enabling the curtain to maintain good toughness and transparency at low temperatures; it improves interlayer bonding and UV resistance through the π-π stacking and hydrogen bonding of organic small molecule reinforcing agents; the overall material exhibits excellent anti-aging, cold resistance and scratch resistance during long-term use, significantly extending service life and improving application stability.

[0006] The objective of this invention can be achieved through the following technical solutions: A high-performance layered PVC door curtain comprises the following raw materials in parts by weight: 80-120 parts modified polyvinyl chloride resin, 5-15 parts 2-vinyl-4-hydroxyacetophenone, 10-25 parts epoxidized soybean oil, 20-40 parts dioctyl phthalate, 2-6 parts calcium-zinc stabilizer, 3-10 parts impact agent, 0.3-1.0 parts light stabilizer, 0.2-0.8 parts lubricant, and 5-15 parts inorganic filler; wherein, the modified polyvinyl chloride resin is a molecular layered structure resin with a polar gradient distribution obtained by synergistic grafting reaction of polyvinyl chloride with γ-glycidyl etheroxypropyltrimethoxysilane and 3,3,4,4,5,5-hexafluoroglutaric acid in an organic solvent; the 2-vinyl-4-hydroxyacetophenone is dispersed in the interlayer as an organic small molecule reinforcing agent, improving the transparency, cold resistance, and anti-aging properties of the door curtain through π-π stacking and hydrogen bonding.

[0007] Optionally, the modified polyvinyl chloride resin comprises the following raw materials in parts by weight: 80-120 parts of polyvinyl chloride resin, 3-8 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 1-5 parts of 3,3,4,4,5,5-hexafluoroglutaric acid, 0.1-0.5 parts of dicumyl peroxide, and 100-150 parts of toluene.

[0008] Optionally, the preparation method of modified polyvinyl chloride resin includes the following steps: (1) Add polyvinyl chloride resin, γ-glycidyl etheroxypropyltrimethoxysilane, 3,3,4,4,5,5-hexafluoroglutaric acid and toluene into a reaction vessel and stir until homogeneous; (2) Add dicumyl peroxide to carry out the grafting reaction; (3) After the reaction is complete, filter to remove the solvent and dry to obtain modified polyvinyl chloride resin.

[0009] Optionally, the reaction conditions in step (1) are stirring for 10 to 20 minutes under nitrogen protection.

[0010] Optionally, the grafting reaction conditions in step (2) are to react at 70-80°C for 2-4 hours.

[0011] Optionally, the reaction conditions for step (3) are vacuum drying at 80°C for 6 to 8 hours.

[0012] Optionally, the calcium-zinc stabilizer is a composite stabilizer composed of calcium stearate and zinc stearate mixed in a mass ratio of 1:1 to 2:1; the impact agent is composed of methyl methacrylate-butadiene-styrene copolymer; the light stabilizer is a hindered amine light stabilizer; the lubricant is composed of polyethylene wax and stearic acid mixed in a mass ratio of 1:1 to 3:1; and the inorganic filler is talc powder surface-modified with a silane coupling agent.

[0013] Optionally, a method for preparing a high-performance layered PVC door curtain includes the following steps: S1, Modified polyvinyl chloride resin, 2-vinyl-4-hydroxyacetophenone, epoxidized soybean oil, dioctyl phthalate, calcium zinc stabilizer, impact agent, light stabilizer, lubricant and inorganic filler are added to a high-speed mixer and mixed evenly to obtain a premix. S2, the premix is ​​fed into a twin-screw extruder for melt plasticization and granulation to obtain composite granules; S3, the composite granules are extruded into shape using a three-layer co-extrusion equipment, cooled, shaped, and cut to obtain a high-performance layered PVC door curtain.

[0014] Optionally, the mixing conditions in step S1 are to mix at 80-90°C and a speed of 1500-1800 rpm for 10-15 minutes until the material is evenly dispersed; the extrusion conditions in step S2 are that the temperature zones of the twin-screw extruder are 160°C, 175°C, 185°C, and 190°C respectively, the die head temperature is 190°C, and the screw speed is 180-220 rpm.

[0015] Optionally, the molding conditions in step S3 are: a three-layer co-extrusion die temperature of 185-195°C, a traction rate of 4-6 m / min, and the door curtain product is obtained after being shaped in a cooling water tank.

[0016] The beneficial effects of this invention are: This invention utilizes fluorosilicone bifunctional groups to synergistically graft and modify polyvinyl chloride (PVC) resin, forming a polar gradient distribution structure at the molecular level. This achieves dual regulation of molecular chain flexibility and interfacial energy matching. Simultaneously, it introduces 2-vinyl-4-hydroxyacetophenone, an organic small molecule not previously used in this field. Its π-π stacking and hydrogen-bonded self-assembly properties enable the construction of a stable, micro-ordered network between layers, significantly improving the bonding strength and morphological stability between the layers. This innovative combination achieves molecular-scale synergy at the structural level, balancing flexibility, optical uniformity, and interfacial stability, providing a novel molecular design approach for transparent PVC layer materials. Attached Figure Description

[0017] The invention will now be further described with reference to the accompanying drawings.

[0018] Figure 1 A comparison of the infrared spectra of polyvinyl chloride resin and modified polyvinyl chloride resin; Figure 2 A comparison chart of optical performance test results for samples with different ratios; Figure 3 This is a comparison chart of the interlayer peel strength test results for samples with different formulation ratios. Detailed Implementation

[0019] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.

[0020] Example 1 The purpose of this embodiment is to verify the effect of modified polyvinyl chloride matrix and a small amount of organic small molecule reinforcing agent on improving the basic performance of door curtains under low ratio conditions.

[0021] S1, weigh 80 parts of polyvinyl chloride resin, 3 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 1 part of 3,3,4,4,5,5-hexafluoroglutaric acid, 0.1 parts of dicumyl peroxide, and 100 parts of toluene, and add them to a three-necked flask equipped with a stirrer. Stir for 15 minutes under nitrogen protection to ensure that the components are fully dispersed. Then heat to 70°C, add initiator dropwise, and continue the reaction for 2 hours. After the reaction is completed, cool to room temperature, filter to remove the solvent, and vacuum dry at 80°C for 6 hours to obtain modified polyvinyl chloride resin. S2. 80 parts of modified polyvinyl chloride resin, 5 parts of 2-vinyl-4-hydroxyacetophenone, 10 parts of epoxidized soybean oil, 20 parts of dioctyl phthalate, 2 parts of calcium-zinc stabilizer, 3 parts of impact agent, 0.3 parts of light stabilizer, 0.2 parts of lubricant, and 5 parts of inorganic filler were added to a high-speed mixer and mixed at 1500 rpm for 12 minutes at 85°C to obtain a homogeneous premix. The premix was then fed into a twin-screw extruder, with temperature zones set at 160°C, 175°C, 185°C, and 190°C, a die head temperature of 190°C, and a screw speed of 200 rpm for melt plasticizing and granulation to obtain composite granules.

[0022] S3 involves extruding the composite granules into a film using a three-layer co-extrusion machine at a die temperature of 185℃, a traction speed of 4m / min, and a cooling water bath temperature of 25℃. After shaping and cutting, a transparent and flexible layered PVC door curtain is obtained. This sample exhibits high transparency, a smooth surface, and does not become brittle at a low temperature of -30℃.

[0023] Example 2 The purpose of this embodiment is to verify the ultimate performance and structural stability of the door curtain under conditions of high content of modified components and reinforcing agents.

[0024] S1, weigh 120 parts of polyvinyl chloride resin, 8 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 5 parts of 3,3,4,4,5,5-hexafluoroglutaric acid, 0.5 parts of dicumyl peroxide, and 150 parts of toluene, and stir for 10 minutes under nitrogen protection; heat to 80℃ and react for 4 hours. After the reaction is complete, cool to room temperature, filter to remove the solvent, and vacuum dry for 8 hours to obtain modified polyvinyl chloride resin;

[0025] S2, 120 parts of modified polyvinyl chloride resin, 15 parts of 2-vinyl-4-hydroxyacetophenone, 25 parts of epoxidized soybean oil, 40 parts of dioctyl phthalate, 6 parts of calcium-zinc stabilizer, 10 parts of impact agent, 1.0 part of light stabilizer, 0.8 parts of lubricant, and 15 parts of inorganic filler are added to a high-speed mixer and mixed at 1800 rpm for 15 minutes at 90°C. Then, the mixture is fed into a twin-screw extruder with temperature zones set to 165°C, 180°C, 190°C, and 190°C, a die head temperature of 190°C, and a screw speed of 220 rpm for melt plasticizing and granulation to obtain highly uniform composite granules. S3 involves extruding composite granules through a three-layer co-extrusion machine at a die temperature of 195℃ and a traction rate of 6m / min. After cooling and shaping in a water bath, the resulting high-performance layered PVC curtain exhibits uniform thickness, high transparency, and excellent bending resistance. This sample does not crack at a low temperature of -40℃, and its interlayer peel strength is increased by approximately 45%.

[0026] Example 3 The purpose of this embodiment is to verify the overall performance and production process stability of the door curtain under intermediate mixing ratio conditions.

[0027] S1, weigh 100 parts of polyvinyl chloride resin, 5 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 3 parts of 3,3,4,4,5,5-hexafluoroglutaric acid, 0.3 parts of dicumyl peroxide, and 120 parts of toluene. Stir for 15 minutes under nitrogen protection, then heat to 75°C and react for 3 hours. After the reaction is complete, filter to remove the solvent, and dry under vacuum at 80°C for 6 hours to obtain modified polyvinyl chloride resin. Figure 1 Infrared spectral comparison results showed that unmodified PVC exhibited typical C–H, CH2, and C–Cl vibrational peaks at 2925, 2850, 1430, and 690 cm⁻¹, indicating a common PVC structure. The modified PVC resin spectrum showed significant new peaks: enhanced O–H stretching vibration at 3430 cm⁻¹, indicating the introduction of hydroxyl or silanol groups; a prominent C=O stretching vibration at 1730 cm⁻¹, indicating grafting of hexafluoroglutaric acid onto the PVC backbone; C–F and C–O–C absorption peaks at 1215 and 1155 cm⁻¹, reflecting the incorporation of fluorine and the ring-opening reaction of epoxy groups; and enhanced Si–O–C characteristic peaks at 1080 and 1030 cm⁻¹, proving successful silane grafting. Comprehensive analysis showed that the modified PVC molecular structure transformed from a nonpolar chain to a polar gradient layered structure, verifying the successful achievement of synergistic grafting modification.

[0028] S2, 100 parts of modified polyvinyl chloride resin, 10 parts of 2-vinyl-4-hydroxyacetophenone, 15 parts of epoxidized soybean oil, 30 parts of dioctyl phthalate, 4 parts of calcium-zinc stabilizer, 6 parts of impact agent, 0.5 parts of light stabilizer, 0.5 parts of lubricant, and 10 parts of inorganic filler are added to a high-speed mixer and mixed at 1600 rpm for 12 minutes at 85°C to obtain a premix; the premix is ​​then fed into a twin-screw extruder, with the temperature zones set sequentially to 160°C, 175°C, 185°C, and 190°C, the die head temperature set to 190°C, and the screw speed set to 200 rpm for melt plasticizing and granulation to obtain composite granules; S3 involves extruding composite granules through a three-layer co-extrusion machine at a die temperature of 190℃ and a traction rate of 5m / min. After being shaped in a cooling water bath at 25℃, the material is cut to obtain a high-performance layered PVC curtain. The finished product has a light transmittance of 93%, an elongation at break of 265%, and remains flexible even at a low temperature of -35℃.

[0029] Comparative Example 1 The purpose was to verify the changes in curtain performance and interface stability when only silane grafting was performed.

[0030] S1, weigh 100 parts of polyvinyl chloride resin, 5 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 0 parts of 3,3,4,4,5,5-hexafluoroglutaric acid, 0.3 parts of dicumyl peroxide, and 120 parts of toluene. Stir for 15 minutes under nitrogen protection, then heat to 75°C and react for 3 hours. After the reaction is complete, filter to remove the solvent, and dry under vacuum at 80°C for 6 hours to obtain modified polyvinyl chloride resin. S2, 100 parts of modified polyvinyl chloride resin, 10 parts of 2-vinyl-4-hydroxyacetophenone, 15 parts of epoxidized soybean oil, 30 parts of dioctyl phthalate, 4 parts of calcium-zinc stabilizer, 6 parts of impact agent, 0.5 parts of light stabilizer, 0.5 parts of lubricant, and 10 parts of inorganic filler are added to a high-speed mixer and mixed at 1600 rpm for 12 minutes at 85°C to obtain a premix; the premix is ​​then fed into a twin-screw extruder, with the temperature zones set sequentially to 160°C, 175°C, 185°C, and 190°C, the die head temperature set to 190°C, and the screw speed set to 200 rpm for melt plasticizing and granulation to obtain composite granules; S3, the composite granules are extruded through a three-layer co-extrusion machine at a die temperature of 190°C and a traction rate of 5 m / min. After being shaped in a cooling water bath at 25°C, the material is cut to obtain a layered PVC door curtain. The finished product has a light transmittance of approximately 91% and an elongation at break of approximately 240%. Slight hardening occurs at a low temperature of −32°C, and the interlayer peel strength is lower than that in Example 3.

[0031] Comparative Example 2 The purpose was to verify the changes in curtain performance and interlayer compatibility when only fluorinated diacid grafting was performed.

[0032] S1, weigh 100 parts of polyvinyl chloride resin, 0 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 3 parts of 3,3,4,4,5,5-hexafluoroglutaric acid, 0.3 parts of dicumyl peroxide, and 120 parts of toluene. Stir for 15 minutes under nitrogen protection, then heat to 75°C and react for 3 hours. After the reaction is complete, filter to remove the solvent, and dry under vacuum at 80°C for 6 hours to obtain modified polyvinyl chloride resin. S2, 100 parts of modified polyvinyl chloride resin, 10 parts of 2-vinyl-4-hydroxyacetophenone, 15 parts of epoxidized soybean oil, 30 parts of dioctyl phthalate, 4 parts of calcium-zinc stabilizer, 6 parts of impact agent, 0.5 parts of light stabilizer, 0.5 parts of lubricant, and 10 parts of inorganic filler are added to a high-speed mixer and mixed at 1600 rpm for 12 minutes at 85°C to obtain a premix; the premix is ​​then fed into a twin-screw extruder, with the temperature zones set sequentially to 160°C, 175°C, 185°C, and 190°C, the die head temperature set to 190°C, and the screw speed set to 200 rpm for melt plasticizing and granulation to obtain composite granules; S3, the composite granules are extruded through a three-layer co-extrusion machine at a die temperature of 190°C and a traction rate of 5m / min. After being shaped in a cooling water bath at 25°C, they are cut to obtain a layered PVC door curtain. The finished product has a light transmittance of approximately 90%, an elongation at break of approximately 230%, decreased flexibility at low temperature (−31°C), and poorer interface stability than in Example 3.

[0033] Comparative Example 3 The purpose was to verify the changes in interlayer bonding and weather resistance when the organic small molecule reinforcing agent was removed.

[0034] S1, weigh 100 parts of polyvinyl chloride resin, 5 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 3 parts of 3,3,4,4,5,5-hexafluoroglutaric acid, 0.3 parts of dicumyl peroxide, and 120 parts of toluene. Stir for 15 minutes under nitrogen protection, then heat to 75°C and react for 3 hours. After the reaction is complete, filter to remove the solvent, and dry under vacuum at 80°C for 6 hours to obtain modified polyvinyl chloride resin. S2, 100 parts of modified polyvinyl chloride resin, 0 parts of 2-vinyl-4-hydroxyacetophenone, 15 parts of epoxidized soybean oil, 30 parts of dioctyl phthalate, 4 parts of calcium-zinc stabilizer, 6 parts of impact agent, 0.5 parts of light stabilizer, 0.5 parts of lubricant, and 10 parts of inorganic filler are added to a high-speed mixer and mixed at 1600 rpm for 12 minutes at 85°C to obtain a premix; it is then fed into a twin-screw extruder, with the temperature zones set sequentially to 160°C, 175°C, 185°C, and 190°C, the die head temperature set to 190°C, and the screw speed set to 200 rpm for melt plasticizing and granulation to obtain composite granules; S3, the composite granules are extruded through a three-layer co-extrusion machine at a die temperature of 190°C and a traction rate of 5 m / min. After being shaped in a cooling water bath at 25°C, they are cut to obtain a layered PVC door curtain. The finished product has a light transmittance of approximately 92% and an elongation at break of approximately 235%. It can still be used at a low temperature of -33°C, but the interlayer peel strength is significantly lower than that of Example 3, and the UV aging resistance retention rate is reduced.

[0035] Performance testing 1. Test methods for light transmittance and haze This test was used to evaluate the optical performance of PVC door curtains. Samples were cut into flat sheets 2mm thick and 100mm x 100mm in size, with clean surfaces free of bubbles and scratches. Transmittance and haze were measured using an integrating sphere haze meter. The visible light range was scanned under standard light source conditions, and the transmittance value at 550nm was taken as the representative value. Each sample was measured three times at different locations, and the average value was taken. The test results were used to compare the uniformity of the material's internal structure and the differences in interfacial refraction. High transmittance and low haze indicate a uniform molecular layer structure and good interfacial matching.

[0036] 2. Low-temperature embrittlement resistance test method This test evaluates the flexibility and impact resistance of door curtains in low-temperature environments. Samples are cut into 100mm × 150mm pieces and placed in an adjustable low-temperature chamber for graded cooling, with each grade separated by 5°C and held for 30 minutes. Immediately after removal, the samples are bent once on a bending fixture with a 5mm bending radius, and the appearance of cracks is observed. The temperature at which the first crack appears is recorded as the embrittlement temperature. If necessary, a drop-weight impact test is performed under the same temperature conditions to observe whether the sample breaks. No cracks or breakage at low temperatures indicate good material flexibility and a stable molecular chain structure.

[0037] 3. Interlayer peel strength test method This test is used to determine the bonding strength between multiple layers of a door curtain structure. A three-layer co-extruded film sample is cut into strips of 25mm × 200mm along the interlayer boundaries, with a 50mm peel cut at one end. A universal testing machine is used to perform a 180° peel test at 23℃ and a speed of 50mm / min. The tensile force during the stable peel stage is recorded, and the failure morphology is observed. If the failure mainly occurs within the layers and the peel force is stable, it indicates strong interlayer bonding; if interface separation occurs or the peel force significantly decreases, it indicates insufficient structural adhesion.

[0038] 4. Test method for UV aging resistance This test evaluates the weather resistance of door curtains under ultraviolet (UV) irradiation. Samples are placed in an accelerated UV aging chamber using UVA-340 lamps, with one cycle consisting of 8 hours of illumination at 60°C and 4 hours of condensation at 50°C. After 500 hours and 1000 hours of aging, samples are taken to test tensile strength, elongation at break, and changes in transparency, and surface color and gloss are observed. The results determine the material's resistance to photodegradation; maintaining high mechanical properties and transparency with minimal color change indicates excellent UV stability.

[0039] Table 1 Optical performance test results

[0040] Table 2 Results of Low-Temperature Embrittlement Resistance and Impact Performance Tests

[0041] Table 3 Results of interlayer peel strength test

[0042] Table 4. Results of UV aging resistance test

[0043] The test results in Tables 1 to 4 show that Examples 1 to 3 exhibit a gradual improvement trend in all performance aspects, while Comparative Examples 1 to 3 show significantly poor overall performance. This fully demonstrates that the synergistic grafting modification of fluorosilicone bifunctional groups and the organic small molecule reinforcement mechanism in this invention play a key role in improving the material performance.

[0044] In terms of optical performance, Figure 2 In Example 1, the transmittance was 90.2% and the haze was 1.8%, indicating that the low-proportion modified PVC system had initially improved the molecular chain arrangement, but the interfacial matching was not yet sufficient. In Example 2, after increasing the content of modifier and small molecules, the transmittance increased to 93.1% and the haze decreased to 1.3%, with a smoother interface. Example 3 had the highest transmittance at 93.8% and a haze of only 1.1%, indicating that the polar gradient layer structure formed by fluorosilicone synergistic grafting and the π-π stacking effect between small molecules significantly reduced light scattering, achieving high transparency and optical uniformity. In contrast, Comparative Examples 1 and 2 only underwent single modification, resulting in polarity differences between interfacial layers, causing light to be scattered during propagation and a significant decrease in transmittance. Comparative Example 3 lacked the filling and interfacial harmonizing effect of small molecule reinforcing agents, resulting in internal light reflection and hazy turbidity.

[0045] Regarding low-temperature embrittlement resistance, Example 1 exhibited an embrittlement temperature of -30°C, which basically meets the requirements for use below room temperature, but slight cracks appeared at -35°C. Example 2, after fluorosilicone modification and reinforcement, saw its embrittlement temperature drop to -38°C, with an impact integrity rate of 92%, and significantly improved flexibility. Example 3 performed best, with an embrittlement temperature of -40°C, an impact integrity rate of 96%, and remained flexible and crack-free at low temperatures. Conversely, the single-modification systems of Comparative Examples 1 and 2 both showed cracks below -25°C, indicating that monofunctional groups cannot form a stable flexible structure. Although Comparative Example 3 had moderate modification, the lack of hydrogen-bonding softening effect from 2-vinyl-4-hydroxyacetophenone resulted in uneven intermolecular energy transfer, leading to significant stress concentration during low-temperature impact.

[0046] In the interlayer peel strength test Figure 3 In Example 1, the peel strength was 6.8 N / cm, indicating that while fluorosilicone grafting can improve interfacial compatibility, the bonding strength is still limited. In Example 2, the peel strength increased to 7.9 N / cm, with interlayer failures all occurring within the layers, indicating more effective polarity regulation. Example 3 showed the highest peel strength at 8.4 N / cm, with stable interlayer bonding and a clean fracture surface, fully demonstrating that the fluorosilicone bifunctional structure and small molecule stacking network synergistically enhanced interfacial bonding. Comparative Examples 1 and 2 had peel strengths of only about 5 N / cm, both showing interfacial failure and significant interlayer slip; although Comparative Example 3 was slightly higher than the single-modification system, the bonding strength was still insufficient due to the lack of molecular bridging structures.

[0047] Regarding UV aging resistance, Example 1 showed a strength retention rate of 86% after 1000 hours, with a slight yellowing tinge. Example 2 further improved the retention rate to 88%, and the yellowness index decreased to 2.3, indicating that fluorine can significantly inhibit photo-oxidation. Example 3 exhibited the best overall stability, with a strength retention rate of 90%, an elongation at break retention rate of 86%, and minimal change in transparency, indicating that the high fluorine bond energy and the ability of aromatic small molecules to absorb UV energy and stabilize the conjugated structure, reducing chain breakage. Comparative Examples 1 and 2, lacking a dual protection system, showed severe yellowing and significant strength degradation after aging; Comparative Example 3, although containing modified resin, lacked the assistance of UV-absorbing small molecules, resulting in insufficient anti-aging ability.

[0048] Example 1 demonstrates the basic modification effect of this system, showing superior transparency and flexibility compared to traditional PVC. Example 2 further enhances performance by increasing the proportion of the modified component, but due to the excessively high polarity gradient, some flexibility is slightly reduced. Example 3 achieves the optimal balance, reaching the best overall level in optical, mechanical, and weather resistance properties. The results of comparing Examples 1-3 indicate that single-functional group modification cannot simultaneously address the coordination between interfacial energy and molecular flexibility; the combination of inorganic and organic phases is insufficient; and the lack of small-molecule reinforcing network support leads to significant deterioration in optical and mechanical properties. In summary, the excellent performance of Example 3 fully verifies the creativity and significant technical effects of the synergistic modification and molecular structure design of this invention.

Claims

1. A high-performance layered PVC door curtain, characterized in that, The product comprises the following raw materials in parts by weight: 80-120 parts modified polyvinyl chloride resin, 5-15 parts 2-vinyl-4-hydroxyacetophenone, 10-25 parts epoxidized soybean oil, 20-40 parts dioctyl phthalate, 2-6 parts calcium-zinc stabilizer, 3-10 parts impact agent, 0.3-1.0 parts light stabilizer, 0.2-0.8 parts lubricant, and 5-15 parts inorganic filler. The modified polyvinyl chloride resin is a molecular layer structure resin obtained by synergistic grafting of polyvinyl chloride with γ-glycidyl etheroxypropyltrimethoxysilane and 3,3,4,4,5,5-hexafluoroglutaric acid in an organic solvent. The 2-vinyl-4-hydroxyacetophenone acts as an organic small molecule reinforcing agent dispersed between the layers, improving the transparency, cold resistance, and anti-aging properties of the curtain through π-π stacking and hydrogen bonding.

2. The high-performance layered PVC door curtain according to claim 1, characterized in that, The modified polyvinyl chloride resin comprises the following raw materials in parts by weight: 80-120 parts of polyvinyl chloride resin, 3-8 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 1-5 parts of 3,3,4,4,5,5-hexafluoroglutaric acid, 0.1-0.5 parts of dicumyl peroxide, and 100-150 parts of toluene.

3. A high-performance layered PVC door curtain according to any one of claims 1 or 2, characterized in that, The preparation method of the modified polyvinyl chloride resin includes the following steps: (1) Add polyvinyl chloride resin, γ-glycidyl etheroxypropyltrimethoxysilane, 3,3,4,4,5,5-hexafluoroglutaric acid and toluene into a reaction vessel and stir until homogeneous; (2) Add dicumyl peroxide to carry out the grafting reaction; (3) After the reaction is complete, filter to remove the solvent and dry to obtain modified polyvinyl chloride resin.

4. The high-performance layered PVC door curtain according to claim 3, characterized in that, The reaction conditions for step (1) are stirring for 10 to 20 minutes under nitrogen protection.

5. A high-performance layered PVC door curtain according to claim 3, characterized in that, The grafting reaction conditions in step (2) are to react at 70-80°C for 2-4 hours.

6. A high-performance layered PVC door curtain according to claim 3, characterized in that, The reaction conditions for step (3) are vacuum drying at 80°C for 6 to 8 hours.

7. A high-performance layered PVC door curtain according to claim 1, characterized in that, The calcium-zinc stabilizer is a composite stabilizer composed of calcium stearate and zinc stearate mixed in a mass ratio of 1:1 to 2:1; the impact agent is composed of methyl methacrylate-butadiene-styrene copolymer; the light stabilizer is a hindered amine light stabilizer; the lubricant is composed of polyethylene wax and stearic acid mixed in a mass ratio of 1:1 to 3:1; and the inorganic filler is talc powder surface-modified with a silane coupling agent.

8. A method for preparing a high-performance layered PVC door curtain, wherein the high-performance layered PVC door curtain is as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1, Modified polyvinyl chloride resin, 2-vinyl-4-hydroxyacetophenone, epoxidized soybean oil, dioctyl phthalate, calcium zinc stabilizer, impact agent, light stabilizer, lubricant and inorganic filler are added to a high-speed mixer and mixed evenly to obtain a premix. S2, the premix is ​​fed into a twin-screw extruder for melt plasticization and granulation to obtain composite granules; S3, the composite granules are extruded into shape using a three-layer co-extrusion equipment, cooled, shaped, and cut to obtain a high-performance layered PVC door curtain.

9. The method for preparing a high-performance layered PVC door curtain according to claim 8, characterized in that, The mixing conditions in step S1 are: mixing at 80-90°C and 1500-1800 rpm for 10-15 minutes; the extrusion conditions in step S2 are: the temperature zones of the twin-screw extruder are 160°C, 175°C, 185°C, and 190°C respectively, the die head temperature is 190°C, and the screw speed is 180-220 rpm.

10. The method for preparing a high-performance layered PVC door curtain according to claim 8, characterized in that, The molding conditions for step S3 are: a three-layer co-extrusion die temperature of 185-195℃, a traction rate of 4-6m / min, and the door curtain product is obtained after being shaped in a cooling water tank.